2017
DOI: 10.1080/09613218.2018.1383715
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environmental quality and occupant satisfaction in green-certified buildings

Abstract: Green-building certification systems aim at improving the design and operation of buildings. However, few detailed studies have investigated whether a green rating leads to higher occupant satisfaction with indoor environmental quality (IEQ). This research builds on previous work to address this. Based on the analysis of a subset of the Center for the Built Environment Occupant Indoor Environmental Quality survey database featuring 11,243 responses from 93 Leadership in Energy and Environmental Design (LEED)-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 89 publications
3
78
1
4
Order By: Relevance
“…Some previous studies [65,66] have shown that occupants in LEED certified buildings tend to be more satisfied with thermal comfort and IAQ than occupants in non-LEED certified buildings, and less satisfied with lighting and acoustic quality. Another study [67] found no correlation between either total LEED points or specific IEQ credits earned and occupant satisfaction. In this study, while LEED score alone was not clearly correlated with measured or perceived IEQ performance, there are insight to be found in the specific points each school earned.…”
Section: Leed Score Discussionmentioning
confidence: 92%
“…Some previous studies [65,66] have shown that occupants in LEED certified buildings tend to be more satisfied with thermal comfort and IAQ than occupants in non-LEED certified buildings, and less satisfied with lighting and acoustic quality. Another study [67] found no correlation between either total LEED points or specific IEQ credits earned and occupant satisfaction. In this study, while LEED score alone was not clearly correlated with measured or perceived IEQ performance, there are insight to be found in the specific points each school earned.…”
Section: Leed Score Discussionmentioning
confidence: 92%
“…One of the main objectives of this Action is assess and evaluate different adaptive facades technologies from an occupantcentered approach and create good-quality survey tools to benchmark and compare the indoor environment in office buildings with adaptive facades Historically, most well-being and satisfaction surveys have been developed with a focus on the indoor environment [2]. Because thermal comfort, visual comfort, acoustic comfort and air quality are the strongest discriminators of well-being and satisfaction of occupants in buildings [7,8]. For example, the UK BUS occupant survey allows benchmarking office buildings against an existing database of case studies [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Human activity is increasing global pollution and causing many environmental problems. Green building is a trend that countries have already prioritized; additionally, countries are constantly and actively improving environmental management implementation (Altomonte, Schiavon, Kent, & Brager, 2019;Paul & Taylor, 2008;Retzlaff, 2008;Zhang, Platten, & Shen, 2011). Practitioners of green building design primarily advocate low-carbon construction and maintenance to conserve energy and reduce environmental pollution (GhaffarianHoseini et al, 2013;Pohekar & Ramachandran, 2004).…”
Section: Introductionmentioning
confidence: 99%